Un écrivain « entre deux rives » : le cas Jules Boissière - Hervé Casini (Lengas)
Jules Boissière (1863-1897) is paradoxically an underrated writer if not forgotten. Except for "Propos d'un intoxiqué" and some yet published short stories from "Fumeurs d'opium", the man and his work still have to discover.Between 2014 and 2016, professor Jean-Yves Casanova publishes some pioneer articles for edition of the Centre d’Étude de la Littérature Occitane, La Revue Littéraire and Littératures.From these numerous lives and writings, Boissière uses two languages-French and Provençal- as means of an artistic production who finds mainly in Indochina a kind of Promised Land, on one hand in verse, on the other hand in prose.As a matter of fact, on the two sides of his special way, Jules Boissière must find again his well-deserved place : the one from a French writer, with occitanist tendency, who loves two languages and, during his Indochina stay , nurtures a highest literary career.